A comprehensive distributed hydrological framework for assessing flood responses to environmental change under multiple human disturbances - Yuhao Wang; Ke Zhang; Edwark Park; Yuning Luo; Jie Liu; Shunzhang Li; Zhaoan Zhang; Yue Kong; Sheng Wang (Journal of Hydrology, 2026)

Flow matching based data augmentation: A novel approach to improve underwater ship-radiated noise classification - Qifan Shen; Yong Wang; Yuning Zhou; Gongao Xia; Kaiyi Zang; Xinwei Luo (Ocean Engineering, 2026)

Exploring fuel-stove and operational impacts on fugitive emissions from indoor biomass combustion - Ke Jiang; Yuning Xie; Tianyao Huang; Yongqiang Zhang; Zhihan Luo; Kai Xiao; Guofeng Shen (Environmental Pollution, 2026)

Isolation and Cytotoxic Activities of Two New 2-Pyridone Alkaloids with Unique Structures from the Beibu Gulf Coral-Derived Acremonium sclerotigenum GXIMD 02501 - Yuning Qin; Xinjian Qu; Miaoping Lin; Hong Zhang; Huangxue Qin; Chenghai Gao; Yonghong Liu; Xuefeng Zhou; Xiaowei Luo (Journal of Ocean University of China, 2026)

Outstanding extrinsic reversible self-healing material for commercial epoxy coating: Dynamic chemistry-based supramolecular interpenetrating polymer networks - Panhua Li; Tingting Luo; Xuanyu Lv; Yuning Shi; Bosen Zhang; Kaixuan Ma; Wanchun Guo; Kesong Tian; Xueai Li; Hui Ying Yang; Haiyan Wang (Chemical Engineering Journal, 2026)

GHydroMod-SIM-DAI v1.0: A new distributed hydrological model capable of dynamically recognizing runoff generation mechanisms and accounting for aboveground and underground anthropogenic impacts - Yuhao Wang; Ke Zhang; Yuning Luo; Qinuo Zhang; Zhijia Li; Cheng Yao; Xinyu Chen; Sheng Wang; Jie Liu; Chuntang Zhang; Shunzhang Li (Journal of Hydrology, 2025)

Initiative invasion promoted photoelectrocatalytic antibacterial function on ZIF-67@CoO@Co foil photoanode - Mengna Ding; Qin Zhang; Fengyan Shi; Liping Zhou; Xinchun Guo; Qiuyue Li; Liulin Luo; Yingchun Miao; Yuning Huo (Chemical Engineering Journal, 2025)

Identification and utilization of a novel large-effect QTL and linked markers for enhancing protein concentration in peanut - Mingjun Wang; Jianbin Guo; Gaorui Jin; Taihua Yang; Weigang Chen; Yuning Chen; Li Huang; Huaiyong Luo; Xiaojing Zhou; Boshou Liao; Huifang Jiang; Nian Liu; et al. (Theoretical and Applied Genetics, 2025)

Identification of candidate genes associated with resistance to aflatoxin production in peanut through genetic mapping and transcriptome analysis - Dongxin Huai; Li Huang; Xiaomeng Xue; Bolun Yu; Yingbin Ding; Gaorui Jin; Hao Liu; Manish K. Pandey; Hari Kishan Sudini; Huaiyong Luo; Xiaojing Zhou; Nian Liu; et al. (Theoretical and Applied Genetics, 2025)

Milk-derived small extracellular vesicles: a new perspective on dairy nutrition - Yuning Zhang; Yingying Lin; Jian He; Sijia Song; Yujia Luo; Yao Lu; Shuxing Chen; Qingyu Wang; Yixuan Li; Fazheng Ren; Huiyuan Guo (Critical Reviews in Food Science and Nutrition, 2024)

iRainSnowHydro v1.0: A distributed integrated rainfall-runoff and snowmelt-runoff simulation model for alpine watersheds - Yuning Luo; Ke Zhang; Yuhao Wang; Sheng Wang; Nan Wu; Shunzhang Li; Qinuo Zhang; Xinyu Chen; Hongjun Bao (Journal of Hydrology, 2024)

Ceratophyllum demersum alleviates microplastics uptake and physiological stress responses in aquatic organisms, an overlooked ability - Weihong Zhao; Xirui Zheng; Jintao Liu; Yanming Sui; Yuning Wang; Pan Luo; Xi Zhu; Wenjing Wu; Wen Gu; Xingyu Liu (Journal of Hazardous Materials, 2024)

Regulation of tumorigenesis and ferroptosis in non-small cell lung cancer by a novel BBOX1-AS1/miR-326/PROM2 axis - Jinlu An; Jiang Shi; Chao Yang; Junfang Luo; Yuning Li; Jie Ren; Yuanjun Lv; Yang Zhang (Molecular and Cellular Biochemistry, 2024)

Perspectives on the highly selective oxidation of copper-mediated C3N4-BiVO4 organic-inorganic hybrid catalysts and the efficient generation of reactive oxygen species - Qian Luo; Yue Chen; Yanjun Zhao; Shan He; Shirui Lv; Yuning Ma; Xintong Liu (Chemical Engineering Journal, 2024)

Changes in properties of human milk under different conditions of frozen storage - Kaibo Wang; Yanfeng Zhao; Sijia Song; Yingying Lin; Yujia Luo; Yafei Zhang; Yi Xue; Wusun Li; Yuning Zhang; Yao Lu; Heng Quan; Hao Zhang; et al. (Food Research International, 2024)

Application and development of zero-valent iron (ZVI)-based materials for environmental remediation: A scientometric and visualization analysis - Qiuju Wu; Yijie Sun; Zijing Luo; Xinyan Li; Yi Wen; Yuning Shi; Xuejia Wu; Xinni Huang; Yiyan Zhu; Chao Huang (Environmental Research, 2024)

A distributed hydrological model for semi-humid watersheds with a thick unsaturated zone under strong anthropogenic impacts: A case study in Haihe River Basin - Xinyu Chen; Ke Zhang; Yuning Luo; Qinuo Zhang; Jiaqi Zhou; Yazhou Fan; Pengnian Huang; Cheng Yao; Lijun Chao; Honghun Bao (Journal of Hydrology, 2023)

Identification of ammonium source for groundwater in the piedmont zone with strong runoff of the Hohhot Basin based on nitrogen isotope - Jinyuan Liu; Jiongliang Yuan; Yilong Zhang; Hengxing Zhang; Yiqing Luo; Yuning Su (Science of The Total Environment, 2023)

Identification of a stable major sucrose-related QTL and diagnostic marker for flavor improvement in peanut - Weitao Li; Li Huang; Nian Liu; Yuning Chen; Jianbin Guo; Bolun Yu; Huaiyong Luo; Xiaojing Zhou; Dongxin Huai; Weigang Chen; Liying Yan; Xin Wang; et al. (Theoretical and Applied Genetics, 2023)

The self-association properties of partially dephosphorylated bovine beta-casein - Sijia Song; Yingying Lin; Yuning Zhang; Yujia Luo; Huiyuan Guo (Food Hydrocolloids, 2023)

Island-like CeO2 decorated LiMn2O4: Surface modification enhancing electrochemical lithium extraction and cycle performance - Guiling Luo; Xiaowei Li; Linlin Chen; Yuning Zhang; Jun Gu; Yanhong Chao; Wenshuai Zhu; Zhichang Liu; Chunming Xu (Chemical Engineering Journal, 2023)

Correction to: Application of Metabolomics to the Discovery of Biomarkers for Ischemic Stroke in the Murine Model: a Comparison with the Clinical Results - Jinjing Jia; Hangyao Zhang; Xiaoyi Liang; Yuning Dai; Lihe Liu; Kaiwen Tan; Ruohan Ma; Jiahuan Luo; Yi Ding; Chaofu Ke (Molecular Neurobiology, 2022)

Application of Metabolomics to the Discovery of Biomarkers for Ischemic Stroke in the Murine Model: a Comparison with the Clinical Results - Jinjing Jia; Hangyao Zhang; Xiaoyi Liang; Yuning Dai; Lihe Liu; Kaiwen Tan; Ruohan Ma; Jiahuan Luo; Yi Ding; Chaofu Ke (Molecular Neurobiology, 2021)

Discovery of two novel and adjacent QTLs on chromosome B02 controlling resistance against bacterial wilt in peanut variety Zhonghua 6 - Huaiyong Luo; Manish K. Pandey; Ye Zhi; Huan Zhang; Siliang Xu; Jianbin Guo; Bei Wu; Haiwen Chen; Xiaoping Ren; Xiaojing Zhou; Yuning Chen; Weigang Chen; et al. (Theoretical and Applied Genetics, 2020)
Key message Two novel and adjacent genomics and candidate genes for bacterial wilt resistance were identified on chromosome B02 in peanut variety Zhonghua 6 using both traditional QTL mapping and QTL-seq methods. Abstract Peanut ( Arachis hypogaea ) is an important oilseed crop worldwide. Utilization of genetic resistance is the most economic and effective approach to control bacterial wilt, one of the most devastating plant diseases, in peanut production. To accelerate the genetic improvement of bacterial wilt resistance (BWR) in peanut breeding programs, quantitative trait locus (QTL) mapping has been conducted for two resistant varieties. In this context, we deployed linkage mapping as well as sequencing-based mapping approach, QTL-seq, to identify genomic regions and candidate genes for BWR in another highly resistant variety Zhonghua 6. The recombination inbred line population (268 progenies) from the cross Xuhua 13 × Zhonghua 6 was used in BWR evaluation across five environments. QTL mapping using both SSR- and SNP-based genetic maps identified a stable QTL ( qBWRB02-1 ) on chromosome B02 with 37.79–78.86% phenotypic variation explained (PVE) across five environments. The QTL-seq facilitated further dissection of qBWRB02-1 into two adjacent genomic regions, qBWRB02-1-1 (2.81–4.24 Mb) and qBWRB02-1-2 (6.54–8.75 Mb). Mapping of newly developed Kompetitive allele-specific PCR (KASP) markers on the genetic map confirmed their stable expressions across five environments. The effects of qBWRB02-1-1 (49.43–68.86% PVE) were much higher than qBWRB02-1-2 (3.96–6.48% PVE) and other previously reported QTLs. Nineteen putative candidate genes affected by 49 non-synonymous SNPs were identified for qBWRB02-1-1 , and ten of them were predicted to code for disease resistance proteins. The major and stable QTL qBWRB02-1-1 and validated KASP markers could be deployed in genomics-assisted breeding (GAB) to develop improved peanut varieties with enhanced BWR.

High-resolution mapping of a major and consensus quantitative trait locus for oil content to a ~ 0.8-Mb region on chromosome A08 in peanut (Arachis hypogaea L.) - Nian Liu; Jianbin Guo; Xiaojing Zhou; Bei Wu; Li Huang; Huaiyong Luo; Yuning Chen; Weigang Chen; Yong Lei; Yi Huang; Boshou Liao; Huifang Jiang (Theoretical and Applied Genetics, 2020)
Key message ddRAD-seq-based high-density genetic map comprising 2595 loci identified a major and consensus QTL with a linked marker in a 0.8-Mb physical interval for oil content in peanut. Abstract Enhancing oil content is an important breeding objective in peanut. High-resolution mapping of quantitative trait loci (QTLs) with linked markers could facilitate marker-assisted selection in breeding for target traits. In the present study, a recombined inbred line population (Xuhua 13 × Zhonghua 6) was used to construct a genetic map based on double-digest restriction-site-associated DNA sequencing (ddRAD-seq). The resulting high-density genetic map contained 2595 loci, and spanned a length of 2465.62 cM, with an average distance of 0.95 cM/locus. Seven QTLs for oil content were identified on five linkage groups, including the major and stable QTL qOCA08.1 on chromosome A08 with 10.14–27.19% phenotypic variation explained. The physical interval of qOCA08.1 was further delimited to a ~ 0.8-Mb genomic region where two genes affecting oil synthesis had been annotated. The marker SNPOCA08 was developed targeting the SNP loci associated with oil content and validated in peanut cultivars with diverse oil contents. The major and stable QTL identified in the present study could be further dissected for gene discovery. Furthermore, the tightly linked marker for oil content would be useful in marker-assisted breeding in peanut.

Review of Chinese atmospheric science research over the past 70 years: Synoptic meteorology - Zhiyong Meng; Fuqing Zhang; Dehai Luo; Zhemin Tan; Juan Fang; Jianhua Sun; Xueshun Shen; Yunji Zhang; Shuguang Wang; Wei Han; Kun Zhao; Lei Zhu; et al. (Science China Earth Sciences, 2019)

Chromosomes A07 and A05 associated with stable and major QTLs for pod weight and size in cultivated peanut (Arachis hypogaea L.) - Huaiyong Luo; Jianbin Guo; Xiaoping Ren; Weigang Chen; Li Huang; Xiaojing Zhou; Yuning Chen; Nian Liu; Fei Xiong; Yong Lei; Boshou Liao; Huifang Jiang (Theoretical and Applied Genetics, 2018)

Development of SSR markers and identification of major quantitative trait loci controlling shelling percentage in cultivated peanut (Arachis hypogaea L.) - Huaiyong Luo; Zhijun Xu; Zhendong Li; Xinping Li; Jianwei Lv; Xiaoping Ren; Li Huang; Xiaojing Zhou; Yuning Chen; Jingyin Yu; Weigang Chen; Yong Lei; et al. (Theoretical and Applied Genetics, 2017)